ChemInform Abstract: The Facile Construction of the Phthalazin‐1(2H)‐one Scaffold via Copper‐Mediated C—H(sp2)/C—H(sp) Coupling under Mild Conditions. Issue 49 (December 2015) - Zhu, Wei; Wang, Bao; Zhou, Shengbin; Liu, Hong
Abstract: The reactions of benzamides [e.g. (I)] and terminal alkynes [e.g. (II)] give isoindolinones [e.g. (III)] via a Cu‐mediated cascade coupling and intramolecular annulation.